The Relationship of Long Suffering With Quality of Life in Diabetes Mellitus Patients - Nurlinda Shafitri R. Paris; Vivien Novarina A. Kasim; Ita Sulistiani Basir; Nirwanto K Rahim (PT.Mantaya Idea Batara, 2023)
The average diabetes mellitus patient at the Puskesmas Telaga has a long-suffering status of ? 3 years with a decreased life quality due to inadequate management of diabetes mellitus (self-care). This research aims to determine the relationship between the duration of illness and quality of life in type II diabetes mellitus patients in the working area of Puskesmas Telaga, Gorontalo Regency. The research employs a cross-sectional method with a sample total of 66 respondents obtained through purposive sampling. Data analysis employs the chi-square test with the Diabetes Quality of Life (DQOL) questionnaire as an instrument. The results indicate that 25 respondents (37.9%) have suffered for ? 3 years with poor life quality related to descreased patient self-care due to boredom and burnout. In addition, long suffering < 3 years with poor life quality, as many as six respondents (9.1%) related to the patient’s unpreparedness in receiving a diagnosis of diabetes mellitus. To conclude, a p-value = 0,041 is obtained so that there was a relationship between duration of illness and life quality in type II diabetes mellitus patients in the working area of Puskesmas Telaga, Gorontalo Regency. It is expected that patients will improve the management of diabetes mellitus and the public health center collaborating with mental nurses regarding stress management for diabetes mellitus patients.